Role of intestinal microbiota composition in colorectal cancer and in the response to neoadjuvant radiochemotherapy previous to surgery - Sanchez Alcoholado, Lidia (UMA Editorial, 2022)
Intestinal-microbiota has been associated with different diseases, among which are obesity and colorectal cancer (CRC), microbiota is assumed to be a possible link between both disorders. Due to this, the composition of the fecal microbiota of patients with CRC with/without obesity was determined in comparison with the microbial profile of healthy-non-obese-controls, in order to unravel the possible relationship of the intestinal-microbiota with the state of inflammation, intestinal permeability, and a bacterial-derivated metabolite, TMAO, all in the context of obesity-associated CRC. Thus, the intestinal-microbiota of patients with CRC and obesity is characterized by the presence of greater abundance of opportunistic pathogens, which can alter the intestinal barrier function and can contribute to inflammatory processes related to CRC by increasing the production of inflammatory molecules (IL-1β, TMAO). On the other hand, gut-microbiota has been linked to the efficacy and toxicity of cancer treatments. Therefore, the identification of composition, abundance and diversity of the intestinal-microbiota that is associated with the response to preoperative-radiochemotherapy of patients with CRC (responders (R) and poor or non-responders (NR)) was determined, as well as the variations in concentrations of different bacterial-metabolites (polyamines, SCFAs). No significant changes were found in the diversity and composition of the intestinal-microbiota with exception of a significant decrease in Fusobacterium, Escherichia, Klebsiella and an increase in Bifidobacterium at post-treatment time compared to baseline.
Also, a significant increase in the diversity and richness of R compared to NR was observed, with unfavorable pro-inflammatory bacterial taxa prevailing in the NR, and a significant increase in probiotics and butyrate-producing-bacteria in R. Furthermore, NR had significantly higher levels of some acetyl derivatives of polyamines and serum zonulin and significantly lower levels of fecal butyric acid than R. Suggesting that baseline intestinal composition in CRC patients is important in predicting the response of the gut microbiome to neoadyuvant radiochemotherapy.
Keywords: Cáncer colorrectal - Tesis doctorales; Cáncer colorrectal - Tratamiento - Tesis doctorales; Microbiota; Colorectal cancer; Radiochemotherapy